Patterns of medical pluralism among adults: results from the 2001 National Health Interview Survey in Taiwan - Shih, Chun-Chuan (BioMed Central, 2010)
BACKGROUND: Medical pluralism (MP) can be defined as the employment of more than one medical system or the use of both conventional and complementary and alternative medicine (CAM) for health and illness. A population-based survey and linkage with medical records was conducted to investigate MP amongst the Taiwanese population. Previous research suggests an increasing use of CAM worldwide. METHODS: We collected demographic data, socioeconomic information, and details about lifestyle and health behaviours from the 2001 Taiwan National Health Interview Survey. The medical records of interviewees were obtained from National Health Insurance claims data with informed consent. In this study, MP was defined as using both Western medicine and traditional Chinese medicine (TCM) services in 2001. The odds ratio (OR) and 95% confidence interval (CI) were estimated for factors associated with adopting MP in univariate and multiple logistic regression. RESULTS: Among 12,604 eligible participants, 32.5% adopted MP. Being female (OR = 1.44, 95% CI = 1.30 - 1.61) and young (OR = 1.38, 95% CI = 1.15 - 1.66) were factors associated with adopting MP in the multiple logistic regression. People with healthy lifestyles (OR = 1.35, 95% CI = 1.19 - 1.53) were more likely to adopt MP than those with unhealthy lifestyles. Compared with people who had not used folk therapy within the past month, people who used folk therapy were more likely to adopt MP. The OR of adopting MP was higher in people who lived in highly urbanised areas as compared with those living in areas with a low degree of urbanisation. Living in an area with a high density of TCM physicians (OR = 2.19, 95% CI = 1.69 - 2.84) was the strongest predictor for adopting MP. CONCLUSION: MP is common in Taiwan. Sociodemographic factors, unhealthy lifestyle, use of folk therapy, and living in areas with a high density of TCM physicians are all associated with MP. People who had factors associated with the adoption of MP may be at risk for adverse health effects from interactions between TCM herbal medicine and WM pharmaceuticals.